The winter queen - Stevenson, Jane 1959- (Houghton Mifflin, 2002)
Seventeenth century royal-in-exile Elizabeth of Bohemia pursues a clandestine relationship with an African prince against the politically unstable and war-threatened climate of the period.
Orig.-Ausg. u.d.T.: Astraea
Keywords: Elizabeth <Queen, consort of Frederick I, King of Bohemia, 1596-1662> -- Fiction; Elisabeth -- Pfalz, Kurfürstin -- 1596-1662; Geschichte; Africans -- Netherlands -- Fiction; Biographical fiction; Freedmen -- Fiction; Historical fiction; Marriages of royalty and nobility -- Fiction; Miscegenation -- Fiction; Queens -- Fiction; Yoruba (African people) -- Fiction; Niederlande; Netherlands -- History -- Wars of Independence, 1556-1648 -- Fiction; Fiktionale Darstellung